Fundamentals of management accounting - Walker, Janet (CIMA official learning system, Paper C1, 2009)
This new edition of CIMA's Official Learning System is published by Elsevier on behalf of CIMA. The Learning System has been written specifically for the new 2010 syllabus in conjunction with the CIMA faculty. This paperback edition includes: * practice questions throughout * complete revision section * topic summaries * recommended reading from a range of journals * CBA style mock exam * Two colour printing throughout * The Official Learning systems are the only study materials endorsed by CIMA * Key sections written by former examiners for the most accurate, up-to-date guidance towards exam success * Complete integrated package incorporating syllabus guidance, full text, recommended articles, revision guides and extensive question practice